2023
DOI: 10.1038/s41419-023-05763-7
|View full text |Cite
|
Sign up to set email alerts
|

Aberrant Cyclin D1 splicing in cancer: from molecular mechanism to therapeutic modulation

Abstract: Cyclin D1 (CCND1), a crucial mediator of cell cycle progression, possesses many mutation types with different mutation frequencies in human cancers. The G870A mutation is the most common mutation in CCND1, which produces two isoforms: full-length CCND1a and divergent C-terminal CCND1b. The dysregulation of the CCND1 isoforms is associated with multiple human cancers. Exploring the molecular mechanism of CCND1 isoforms has offer new insight for cancer treatment. On this basis, the alterations of CCND1 gene are … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(13 citation statements)
references
References 201 publications
1
12
0
Order By: Relevance
“…CCND1 is a crucial regulatory factor in tumor cells, which is capable of promoting tumor cell proliferation and inducing cell cycle arrest at the S phase [ 65 ]. siRNAs targeting CCND1 inhibit cancer progression by inducing apoptosis and suppressing tumor cell stemness and epithelial-mesenchymal transition [ 66 ]. HSP90AA1 can regulate a variety of biological processes.…”
Section: Discussionmentioning
confidence: 99%
“…CCND1 is a crucial regulatory factor in tumor cells, which is capable of promoting tumor cell proliferation and inducing cell cycle arrest at the S phase [ 65 ]. siRNAs targeting CCND1 inhibit cancer progression by inducing apoptosis and suppressing tumor cell stemness and epithelial-mesenchymal transition [ 66 ]. HSP90AA1 can regulate a variety of biological processes.…”
Section: Discussionmentioning
confidence: 99%
“…Epithelial-mesenchymal transition (EMT) (6-8) plays a significant role in tumor invasion and metastasis, with associated features including the high expression of cyclin D1 and loss of expression of E-cadherin. Previous studies have suggested that decreased expression of Ecadherin promotes poor adhesion and contributes to invasiveness and a poor prognosis (9)(10)(11). Because of the growth pattern characterized by a cell mass with a clear boundary, it is expected that CIN 3-like SCC exhibits an invasion or migration pattern of collective cells.…”
Section: Discussionmentioning
confidence: 99%
“…In terms of therapeutic strategies, research has shown that correcting CCND1 splicing through antisense oligonucleotides (ASO) and small molecule modulators can be effective in cancer therapy ( 67 ). These findings suggest that developing splicing regulatory drugs targeting CCND1 splicing variants could be a promising new option for the treatment of CRC.…”
Section: Tumor-associated Splicing Variants In Crc: From Roles To Pot...mentioning
confidence: 99%